ANALISIS PERBEDAAN LITERASI KEUANGAN MASYARAKAT ANGGOTA CREDIT UNION DENGAN ANGGOTA BAITUT TAMWIL - Warsidi Warsidi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2014)
This study is a survey on Credit Union (CU) Cikal Mas Purwokerto and BaitutTamwil Muhammadiyah (BTM) Dana Mentari Patikraja members in Banyumas. Theaims of this study are to determine: (1) The differences of financial literacy levels between CU Cikal Mas Purwokerto and BTM Dana Mentari Patikraja members at thethree aspects i.e. behaviors, knowledge and attitudes, (2) The level of sharia aspectsknowledge of BTM Dana Mentari Patikraja members, (3) The implementation of interest system of CU Cikal Mas Purwokerto, and (4) The implementation of profit sharingsystem of BTM Dana Mentari Patikraja.The population in this study are individuals in Banyumas who grouped into twogroups, i.e. the members of Credit Union Cikal Mas Purwokerto and the members ofBaitut TamwilMuhammadiyah Dana Mentari Patikraja. There were 60 respondentstaken in this study which consisted of 30 respondents for each group. Based on the research and analysis of data using different test Mann Whitney U showed that: (1)Thereare differences between the financial literacy levels of CU Cikal Mas Purwokertomembers and BTM Dana Mentari Patikraja members viewed from three aspects: behaviors, knowledge and attitudes,(2) The level of sharia aspects knowledge of BTMDana Mentari Patikraja members are relatively low, (3) The implementation of interest system in CU Cikal Mas Purwokerto as according to the theory that the loan interest relatively smaller than the saving interest, it known based on interview with managers of CU Cikal Mas Purwokerto, and (4) The implementation of profit sharing system in BTM Dana Mentari Patikrajaas according to the theory used by Islamic financial institutions that profit sharing agreement to both parties when the contract is underway.